Enhancing Students’ Self-Confidence from Disharmonious Families through Group Guidance with Sociodrama Technique - Kurniawan, Drajat Edy; Saputri, Almadia Qosita Janah (Buletin Konseling Inovatif, 2025)
Adolescence is a developmental phase full of challenges, particularly for students from disharmonious family backgrounds who are vulnerable to low self-confidence. This study aims to enhance students’ self-confidence through group guidance services using the sociodrama technique at a public junior high school in Yogyakarta. The research employed a quantitative approach with a one-group pretest–posttest design. The subjects consisted of six eighth-grade students identified as coming from disharmonious families and having low self-confidence. The instrument used was a self-confidence scale that included indicators of belief in one’s abilities, courage to express opinions, and ability to face challenges. Data were analyzed using a paired sample t-test. The results showed an increase in the average self-confidence score from 46.67 (low category) in the pretest to 71.67 (medium category) in the posttest, with a difference of 25.00. The hypothesis test produced a significance value of 0.000 (p < 0.05), indicating a significant difference between before and after the intervention. These findings demonstrate that group guidance with the sociodrama technique is effective in improving the self-confidence of students from disharmonious families. Thus, the sociodrama technique can be considered an alternative guidance strategy in schools to help students cope with psychological and social problems caused by unfavorable family conditions.